Tactics for overcoming challenges of institutional complexity in boundary crossing research environments - Hendrik Woiwode (WZB Berlin Social Science Center, 2021)
Interdisciplinary research is intensely promoted, but challenged by academic field level demands that hinder the realization of its potential. This paper builds on a qualitative study and asks what means managers use to overcome barriers to interdisciplinary research. First, the study develops a conceptual framework that is based on an institutional logics approach and illustrates contradicting implications of a corporate logic and professional logic scholars are embedded in. Second, the study identifies three tensions that result from coexisting institutional logics and illustrates tactics used to overcome these tensions: Balancing epistemological tensions through boundary objects; Balancing identity tensions through identity work; Balancing evaluative tensions through performance indicators. These tactics help to overcome discrepancies between formal descriptions of interdisciplinary units and the activity structure within these units. Besides its practical relevance for research management and science policy, the results deliver reference points for theory-development in the field of higher education.
Keywords: 300; research governance; interdisciplinary research; grand challenges; institutional complexity